Pendekatan Pembelajaran PKN MIS Fajar Shiddiq - Abdulgani Jamora Nasution; Rodiatul Hasanah Lubis; Annisa Rahimah Lubis; Siti Munawwaroh; Farhan Syaukani (EduInovasi: Journal of Basic Educational Studies, 2023)
Citizenship Education (PKn) in elementary schools has an important meaning for students in the formation of private citizens who understand and are able to exercise their rights and obligations to become intelligent, skilled and characterized Indonesian citizens mandated in Pancasila and the 1945 Constitution. Learning is a process that is carried out by providing education and training to students to achieve learning outcomes. By using several approaches such as (1). Student-oriented or student-centered learning approach (student centered approach) and (2). Teacher-oriented or teacher-centered learning approach (teacher centered approach). Based on the explanation above, the title "PKN MIS Fajar Shiddiq Learning Approach" can be raised. Based on the title, background and formulation of the problem to be studied, the authors use descriptive qualitative research methods. From the results of observations and research interviews, problems were found regarding the learning approach at MIS Fajar Shiddiq regarding the PKN learning approach used by teachers at the school. Keywords : Learning approaches, PKN subject